2016
DOI: 10.1103/physrevb.94.205202
|View full text |Cite
|
Sign up to set email alerts
|

Insulator to semimetallic transition in conducting polymers

Abstract: We report a multiscale modeling of electronic structure of a conducting polymer poly(3,4-ethylenedioxythiopehene) (PEDOT) based on a realistic model of its morphology. We show that when the charge carrier concentration increases, the character of the density of states (DOS) gradually evolves from the insulating to the semimetallic, exhibiting a collapse of the gap between the bipolaron and valence bands with the drastic increase of the DOS between the bands. The origin of the observed behavior is attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 52 publications
2
50
0
1
Order By: Relevance
“…A schematic illustration of a formation of the band structure in PEDOT thin films is presented in Figure (for details see ref. ). A single undoped PEDOT chain has a band gap around E g ≈ 1.7 eV, see Figure a.…”
Section: Introduction and Formulation Of The Problemmentioning
confidence: 99%
“…A schematic illustration of a formation of the band structure in PEDOT thin films is presented in Figure (for details see ref. ). A single undoped PEDOT chain has a band gap around E g ≈ 1.7 eV, see Figure a.…”
Section: Introduction and Formulation Of The Problemmentioning
confidence: 99%
“…1(e) (only energies above 0.1 eV from the Gaussian mean value are taken into account). Here it may be pointed out that the energy levels associated with neighboring nodes might be correlated because the electrostatic potential around the PEDOT chain is correlated with the positions of the counterions [50,51]. To keep our model on a tractable level we do not account for such correlation because this would require full quantum mechanical calculation over the whole system.…”
Section: (A)mentioning
confidence: 99%
“…However in PEDOT where chains are relatively short, it has been shown that the carriers can be delocalized over one entire single chain [50]. Thus, for simplicity, we choose a spatial position of all nodes in the geometrical centers of corresponding PEDOT chains.…”
Section: (A)mentioning
confidence: 99%
See 2 more Smart Citations